Attracting millennial consumers in the digital age - Grodzki, Erika; Powers, Stefanie; Burnstine, Andrew (Scripta Neophilologica Posnaniensia, 2019)
This study focuses on the recent fall of many large scale department stores (Macy’s, J. C. Penney Company, Sear’s, Kmart) and other retail, pharmacy and grocery stores (Bebe, Whole Foods, CVS, Chico’s, Limited, Radio Shack, Game Stop) across the United States. The researchers set out to discover why stores that have existed for years suddenly had to shut down physical locations. The researchers hypothesized that these retail outlets have failed to properly attract millennial consumers. Marketers are endlessly attempting to find solutions on how to best attract millennials in this digital age. What appears to be evident, though, is that the habits of this demographic prefer the ease provided by online shopping. Secondary sources were reviewed to determine exactly why the stores have fallen. The millennial culture was a key component of the study. The results suggest that the stores failed due to improper targeting and in-store attraction.